To Disclose or not to Disclose? That is the Question in Collaborative Law. (27th January 2020) - Hoffman, David A.; Schepard, Andrew
Abstract : Collaborative Law (CL) is a dispute resolution process increasingly used in family law and divorce designed to encourage problem solving negotiations by parties represented by counsel. Many states have adapted legislation to authorize and facilitate CL and thousands of lawyers have been trained in the CL process. CL lawyers and participants sign a Participation Agreement in which they agree that the lawyers will be disqualified if the CL process terminates without settlement. They also promise full and voluntary disclosure of information. The extent of the obligation of disclosure is, however, unclear. Through analysis of an extended hypothetical divorce settlement negotiation, this article advocates that CL lawyers and clients should assume an obligation to disclose material facts without a request from the other side. Traditional legal ethics, based on an adversarial framework, requires only disclosure of information when requested by another party. In addition, in traditional legal ethics, a lawyer cannot disclose information obtained in the course of the lawyer‐client relationship without the client's consent even if material to the negotiation. Some authority regulating CL, however, suggests that CL participants and counsel should disclose material information without a specific request even if a client does not want the information disclosed. In that situation, the CL lawyer should encourage the client to disclose the information but if the client refuses to do so, withdraw from the representation. This Article reviews the arguments for and against an obligation of affirmative disclosure in CL. It suggests that affirmative disclosure obligations should be the subject of discussion between CL participants and lawyers and that CL Participation Agreements should be drafted to establish a clear obligation. Finally, this article identifies key areas for further discussion and research on CL disclosure obligations. Key Points for the Family Court Community: An obligation of affirmative disclosure of material information will increase the fairness and transparency of the CL process for clients and counsel and improve public confidence in it. The best place in the CL process to create an affirmative obligation of disclosure is through inserting appropriate clauses in the Participation Agreement. CL lawyers and parties should discuss their disclosure obligations before signing a Participation Agreement and draft clauses in their Agreements which tailor their disclosure obligations to the specific needs and situation. This Article provides specific suggestions for drafting Participation Agreement provisions that create an obligation of affirmative disclosure for lawyers and participants. This Article also provides an agenda for future discussion of the appropriate balance between confidentiality of client communications and candor in the CL process.